MORPHO-FUNCTIONAL CHARACTERISTICS OF THE SCIATIC NERVE IN THE LATE TERMS OF EXPERIMENTAL PACLITAXEL-INDUCED PERIPHERAL NEUROPATHY UNDER THE CORRECTION OF 2-ETHYL-6-METHYL-3-HYDROXYPYRIDINE SUCCINATE - Ostrovskyi, M.M.; Herashchenko, S.B.; Kulynych, H.B.; Markiv, I.M. (World of Medicine and Biology, 2024)
6 out of 10 patients undergoing treatment for breast cancer, ovarian cancer, and non-small cell lung cancer suffer from the neurotoxicity of the chemotherapy drug Paclitaxel, namely paclitaxel-induced peripheral neuropathy. Among them, one in four needs to reduce the dose, postpone the treatment or even stop the therapy. Previous attempts to use various neuroprotective agents in humans and animal models have not shown sufficient effectiveness in preventing or significantly reducing the intensity of paclitaxel-induced peripheral neuropathy manifestations. The purpose of our study was to establish the effect of the neuroprotective agent 2-ethyl-6-methyl-3-hydroxypyridine succinate on the morpho-functional parameters of the sciatic nerve in experimental paclitaxel-induced peripheral neuropathy. In the experiment, 56 white rats weighing 150–200 g were used. Paclitaxel was administered intraperitoneally to the animals at a dose of 2 mg/kg body weight 4 times after one day, after which the animals were divided into an experimental group – 24 animals that were administered 2-ethyl-6-methyl-3-hydroxypyridine succinate and a control group (24 animals, introduction of water for injections) groups. The results of the “hot plate” tests and von Frey monofilaments showed that the use of 2-ethyl-6-methyl-3-hydroxypyridine succinate reliably reduces the manifestations of peripheral neuropathy caused by paclitaxel on the 28th and 60th days of the experiment. In rats treated with HS, destructive-dystrophic phenomena in the myelin nerve fibers of the sciatic nerve are less pronounced on the 60th, 90th, and 120th days of the experiment. The results of the electron microscopic study are fully consistent with the data of neurophysiological studies and indicate the possibility of using 2-ethyl-6-methyl-3-hydroxypyridine succinate as an effective neuroprotector in paclitaxel-induced peripheral neuropathy.
Keywords: paclitaxel; chemotherapy; neuropathy; nerve; peripheral nervous system